2012
DOI: 10.1016/j.bpj.2012.07.037
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogen-Bonded Networks Along and Bifurcation of the E-Pathway in Quinol:Fumarate Reductase

Abstract: The E-pathway of transmembrane proton transfer has been demonstrated previously to be essential for catalysis by the diheme-containing quinol:fumarate reductase (QFR) of Wolinella succinogenes. Two constituents of this pathway, Glu-C180 and heme b(D) ring C (b(D)-C-) propionate, have been validated experimentally. Here, we identify further constituents of the E-pathway by analysis of molecular dynamics simulations. The redox state of heme groups has a crucial effect on the connectivity patterns of mobile inter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
18
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(20 citation statements)
references
References 82 publications
2
18
0
Order By: Relevance
“…The results obtained indicated that transiently established hydrogen bonding paths involving internal water molecules are responsible for proton transfer from the heme b D ring-C-propionate to Glu C180 (Fig. 7A,B) and that high proton conductance associated with short hydrogen bonding paths could be identified only for the reduced but not the oxidized state of the enzyme [44]. These differences were also associated with a conformational change in the orientation of the Glu C180 side chain in agreement with the predictions from multiconformation continuum electrostatics calculations [45], results from FTIR difference spectroscopy [61] and with alternate conformers in the 1.78 Å resolution crystal structure (PDB ID: 2BS2 [33]).…”
Section: Electroneutrality Of Fumarate Reduction By Menaquinolmentioning
confidence: 89%
See 4 more Smart Citations
“…The results obtained indicated that transiently established hydrogen bonding paths involving internal water molecules are responsible for proton transfer from the heme b D ring-C-propionate to Glu C180 (Fig. 7A,B) and that high proton conductance associated with short hydrogen bonding paths could be identified only for the reduced but not the oxidized state of the enzyme [44]. These differences were also associated with a conformational change in the orientation of the Glu C180 side chain in agreement with the predictions from multiconformation continuum electrostatics calculations [45], results from FTIR difference spectroscopy [61] and with alternate conformers in the 1.78 Å resolution crystal structure (PDB ID: 2BS2 [33]).…”
Section: Electroneutrality Of Fumarate Reduction By Menaquinolmentioning
confidence: 89%
“…It has long been known [42] that the two heme groups have different oxidation-reduction midpoint potentials and an assignment for B. subtilis SQR based on the effects of site-directed mutagenesis has been made [43]. Although in retrospect this assignment is probably correct, the interpretation of such mutagenesis effects can be misleading, as demonstrated recently [44] by the stronger effect of the replacement of a W. succinogenes QFR heme b L ligand on the midpoint potential of heme b H rather than on that of heme b L . A mutagenesis-independent assignment of the "high-potential" heme to b P and the "low-potential" heme to b D was achieved on the basis of structure-based electrostatic calculations [45].…”
Section: Structurementioning
confidence: 93%
See 3 more Smart Citations